The European Union and military force governance and strategy - Norheim-Martinsen, Per M. (Cambridge University Press, 2013)
"The Common Security and Defence Policy maps out how the EU - established primarily to be an economic organisation - can purposefully prepare for and apply the use of military force. In this insightful work, Per M. Norheim-Martinsen argues that, since the EU is not a state but nevertheless does embody some non-intergovernmental characteristics, neither EU studies nor strategic studies is sufficient for fully understanding the Policy itself. Combining the two fields, the author utilises the instrumentality and clarity of the strategic approach, while retaining an understanding of the unique character of the EU as a strategic actor. In so doing, he provides a fruitful conceptual framework for analysing the development of the CSDP, how it functions in practice and how it will continue to evolve in the face of the challenges which lie ahead. This book will appeal to scholars and advanced students of European studies, international relations and strategic studies"--